The Effect of Social Media Addiction, FOMO, and Online Game Addiction on Student Learning Achievement - Wati, Riche Siska; Jatmika, Surya (research, training and philanthropy institution Natural Aceh, 2025)
Student learning achievement is one of the leading indicators in evaluating the success of the educational process. At the higher education level, especially efforts to improve student learning achievement are very crucial. When several students are trapped in social media addiction, FOMO, and online game addiction, the learning atmosphere on campus can become less conducive. Class discussions become quiet, and collaboration between friends becomes minimal, negatively impacting academic development. This study uses a quantitative approach with a comparative causal research type. The variables used are independent and dependent. The independent variables consist of Social Media Addiction, FOMO, and Online Game Addiction. The dependent variable is student learning achievement. The results of the study showed a significance value of the F test of 0.026 <0.05; it can be concluded that the variables consisting of social media addiction, FOMO, and online game addiction simultaneously significantly affect student learning achievement. The results of the study concluded that there is a substantial influence between social media addiction, FOMO, and online game addiction on learning achievement. Partially, students who are addicted to online games can affect learning achievement. Students who are addicted to social media and FOMO may not necessarily affect learning achievement.